An empirical study of student action from ipsative design of feedback processes. Issue 5 (13th July 2022) - Malecka, Bianka; Ajjawi, Rola; Boud, David; Tai, Joanna
Abstract: Feedback is justified when it has a positive influence on students' subsequent performance. Opportunities for student action need therefore to be consciously designed if feedback is to influence learning. In this paper, we discuss how ipsative design of feedback processes, i.e. involving comparison of a student's current performance with a previous similar task, can promote action from feedback. This design-based research was conducted with English for Academic Purposes students. A formative e-portfolio was implemented to facilitate students' access to their past work and feedback comments. Its aim was to explore how students exploit the ipsative design of feedback to build on both their own and teacher's actions. Analysis of student artefacts and interviews indicated that ipsative design prompts student comparison processes. Students were motivated to revisit their goals, make comparisons with previous work, and review peers' work. The effects of the design included motivation to engage with feedback beyond the immediate task and the revisiting of past work and action to improve it. Implications for teachers and curriculum designers are discussed including the need to create conditions for student action from feedback by including interconnected tasks and explicit comparison activities in the courses.